Graphene oxide-PLGA hybrid nanofibres for the local delivery of IGF-1 and BDNF in spinal cord repair. Issue 1 (4th December 2019) - Pan, Su; Qi, Zhiping; Li, Qiuju; Ma, Yue; Fu, Chuan; Zheng, Shuang; Kong, Weijian; Liu, Qinyi; Yang, Xiaoyu
Abstract: Spinal cord injury (SCI) can lead to permanent and severe functional impairment below the lesion level and is still one of the most challenging clinical problems. The treatment of SCI has progressed with the development of tissue engineering techniques. Insulin-like growth factor 1 (IGF-1) and brain-derived neurotrophic factor (BDNF) are growth factors closely related to nerve regeneration. In this study, IGF-1 and BDNF were successfully immobilized on biodegradable graphene oxide (GO)-incorporated PLGA (PLGA/GO) electrospun nanofibres. The effect of PLGA/GO nanofibres with immobilized IGF-1 and BDNF on neurogenesis was investigated in vitro and in vivo utilizing MTT assays, immunofluorescence, motor function detection and histology observations. We demonstrated that PLGA/GO nanofibres loaded with IGF-1 and BDNF not only protected NSCs from oxidative stress induced by H2 O2 but also enhanced NSC proliferation and neuronal differentiation in vitro . The in vivo study of an SCI animal model demonstrated that local delivery of IGF-1 and BDNF immobilized to PLGA/GO nanofibres significantly improved functional locomotor recovery, reduced cavity formation and increased the number of neurons at the injury site. Our study indicated that PLGA/GO is an effective carrier for IGF-1 and BDNF delivery and that immobilization of IGF-1 and BDNF onto PLGA/GO nanofibres has a great potential as a nerve implant for spinal cord injury applications.